Choice Of Water Saturation Model In Log Analysis And Its Implication To Water Saturation Estimates – A Further Investigation - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2012)
Water saturation is one of the most important governing factors in hydrocarbon in place and reserves estimation. Error in the estimation of water saturation may signifi cantly impose bias in the estimation of both quantities. In spite of there are various factors affecting potential error in water saturation estimation, choice in water saturation model(s) appears to play an important factor. This study involves eight water saturation models that are widely used in log analysis up until today. Using the same input data, the eight models have proved themseleves to have produced different water saturation estimates. Using a moderate level of water saturation error of 20% evaluation may result in up to 50% error in the reserves estimates. Observing the wide disparities in the estimated water saturation values yielded by the models used in this study, errors higher than 50% may take place. This evidence should strengthen our awareness over the potential error and careful applications of model(s) – and validation of results – that have to be observed.